RISK MANAGEMENT IN ORGANIC FERTILIZER SUPPLY CHAIN ACTIVITIES - Irine Octaviani; Djoko Koestiono; Anisa Aprilia (Faculty of Animal and Agricultural Science, Diponegoro University, 2020)
Supply chain management is not easy because there are two challenges that must be faced, that is the complexity of the supply chain structure and sudden uncertainty, therefore conditions are vulnerable to various forms of risk. In companies that produce organic fertilizer such as PT. MBA, organic fertilizer supply chain activities have the opportunity to pose risks. The purpose of this research is to identify risks and identify the causes of risk and determine the right strategy to deal with the causes of risk in supply chain activities at PT. MBA. The method used is the House of Risk (HOR) by using five indicators in the SCOR (Supply Chain Operation Reference) model, that is plan, source, manufacture, distribution and return. Risk events are identified and considered priorities, that is delays in receiving raw materials from suppliers, implementation of production not on schedule, no production process activities, unable to meet all requests, decreasing product quality during the process, product quality not in accordance with existing standards and delays product delivery (finished fertilizer) to PT. PKG. The priority risk agent is a risk agent to check inaccurate raw materials. Meanwhile, the handling strategy that is a priority to be implemented, with the hope of being able to prevent the causes of risk is coordination, stock strategy and flexible supply base.